Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1460-9592.2001.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment of the Interventricular Delay of Activation and Correlation to the QRS Width in Dilated Cardiomyopathy

Abstract: The aim of the study was to define criteria for left ventricular pacing in dilated cardiomyopathy (DCM) using an echocardiographic evaluation of interventricular electromechanical delay (IMD) and a correlation of IMD to QRS duration. Standard 12-lead ECG and echocardiography with pulsed Doppler tissue imaging (DTI) were recorded in 35 DCM patients (mean age 58 +/- 11 years) with QRS duration from narrow (80 ms) to broad (222 ms) patterns. The timefor left ventricular activation was evaluated from the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 12 publications
(12 reference statements)
5
102
0
9
Order By: Relevance
“…However, electromechanical coupling assessment by conventional echocardiography remains difficult (20). Recently, the alteration of activation-contraction sequence in LV asynchronism was assessed by determining the delay from the onset of QRS (ECG) to the onset of DTI S m wave (Q-S m time) (24). After chronic hypoxia exposure and monocrotaline treatment, Q-S m time was significantly increased compared with control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, electromechanical coupling assessment by conventional echocardiography remains difficult (20). Recently, the alteration of activation-contraction sequence in LV asynchronism was assessed by determining the delay from the onset of QRS (ECG) to the onset of DTI S m wave (Q-S m time) (24). After chronic hypoxia exposure and monocrotaline treatment, Q-S m time was significantly increased compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DTI, which allows measurement of endocardial velocities, provides more accurate measurements of myocardial motion. The delay from the onset of Q wave (ECG) to the onset of DTI S m wave (Q-S m time) could be likened to the time for RV activation as previously used in left ventricle (LV) asynchrony prognosis (24).…”
mentioning
confidence: 99%
“…Yamada et al reported that progressive myocardial fibrosis leads to dyssynchronous activation of the left and right ventricles and a prolonged QRS duration. 15 Possible clinical consequences of ventricular asynchrony, which presents as prolonged QRS duration on ECG, include abnormal interventricular septal wall motion, a reduction in the peak rate of rise of LV pressure, reduced diastolic filling times, and prolonged duration of MR. These factors all appear to be associated with an unfavorable prognosis in heart failure.…”
Section: Qrs Durationmentioning
confidence: 99%
“…A delay greater than 60 ms between those measurements indicates interventricular dyssynchrony. The limitation of such method is that those measurements are not taken simultaneously [20][21][22] .…”
Section: Ventricular Dyssynchronymentioning
confidence: 99%
“…A delay greater than 60 ms between those measurements indicates interventricular dyssynchrony. The limitation of such method is that those measurements are not taken simultaneously [20][21][22] .Another way to assess delay is through the M mode, in which the time between septal contraction and posterior wall contraction is measured ( fig. 2).…”
mentioning
confidence: 99%